MENEJEMEN PENDIDIKAN ISLAM DALAM PERSEFEKTIF AL QUR’AN DAN HADIST - Sofyan Yahya; Sartaman; Nasrudin Harahap; Nurul Hidayati Murtafiah (Journal of Islamic Education and Learning, 2021)
Al-Qur'an and Hadith are the main sources of Islamic teachings which contain the principles of muamalah and some special rules regarding various aspects of life. Today's Muslims, especially those who adhere to Islamic law, , want whatever is learned and implemented in life to always be oriented towards the Qur'an and hadith. Al-Qurulkarim as the holy book of the Muslims, among others, functions as a "hudan" loaded with various instructions so that humans can become good caliphs on this earth. To obtain these instructions, it is necessary to study the Qur'an itself, so that the Muslims in making plans can actually take the maximum benefit from the contents of the Qur'an which are complex in discussing problems. what has happened, All matters relating to human life, as well as the existence of this nature are contained in the Qur'an